The intergenerational transmission of employers in Canada and Denmark - Paul Bingley; Miles Corak; Niels Westergård-Nielsen (Institute for the Study of Labor (IZA), 2011)
The intergenerational transmission of employers between fathers and sons is a common feature of labour markets in Canada and Denmark, with 30 to 40% of young adults having at some point been employed with a firm that also employed their fathers. This is strongly associated with the first jobs obtained during the teen years, but for four to about six percent it also refers to the main job in adulthood. In both countries the transmission of employers is positively associated with paternal earnings, rising distinctly and sharply at the very top of the father's earnings distribution, and has implications for the intergenerational transmission of earnings. Mobility out of the bottom has little to do with inheriting an employer from the father, while the preservation of high income status is distinctly related to this tendency. These findings stress that child adult outcomes are related to the structure of labour markets, and underscore the role of resources parents have - though information, networks, or direct control of the hiring process - in facilitating the job search of their children.
urn:nbn:de:101:1-201104134151
Keywords: J62; J64; J24; 330; intergenerational mobility; job search; equality of opportunity; Unternehmer; Arbeitsnachfrage; Familie; Generationenbeziehungen; Soziale Mobilität; Arbeitsuche; Bildungschancen; Dänemark; Kanada